2014
DOI: 10.1007/s10995-014-1469-0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association of County-Level Economic Indicators and Child Maltreatment Incidents

Abstract: To evaluate the association between economic indicators (unemployment and mortgage foreclosure rates) and volume of investigated and substantiated cases of child maltreatment at the county level from 1990 to 2010 in the Commonwealth of Pennsylvania. County-level investigated reports of child maltreatment and proportion of investigated cases substantiated by child protective services in the Commonwealth of Pennsylvania were compared with county-level unemployment rates from 1990 to 2010, and with county-level m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 27 publications
(27 reference statements)
5
46
0
Order By: Relevance
“…Neither the study by Wood and colleagues nor the study by Berger and colleagues 18 found an association between unemployment rates and rates of AHT or physical abuse. A study by Frioux and colleagues, 23 however, found that county-level unemployment rates and foreclosure rates were both associated with the rates of investigated and substantiated child maltreatment reports in Pennsylvania from 1990 to 2010. Thus, while there are data to suggest that rates of physical abuse, including AHT, increased in the United States during the recent recession, the specific economic changes associated with this increase remain unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Neither the study by Wood and colleagues nor the study by Berger and colleagues 18 found an association between unemployment rates and rates of AHT or physical abuse. A study by Frioux and colleagues, 23 however, found that county-level unemployment rates and foreclosure rates were both associated with the rates of investigated and substantiated child maltreatment reports in Pennsylvania from 1990 to 2010. Thus, while there are data to suggest that rates of physical abuse, including AHT, increased in the United States during the recent recession, the specific economic changes associated with this increase remain unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Their results indicate that both factors are positively associated with CPS investigations and substantiations. 37 These studies provide evidence suggesting a link between home foreclosure and child maltreatment. However, one cannot assume that these macro-level associations hold at the individual or household level.…”
Section: What This Study Addsmentioning
confidence: 88%
“…This pattern, which is apparent in our raw data and the estimates from our survival analyses, supports findings from prior research linking macro-level foreclosure rates with child maltreatment prevalence. 36,37 An examination of the timing of these events, however, reveals that increased risk of CPS involvement is apparent as much as 12 months before a foreclosure filing, although households continue to be at heightened risk of CPS involvement through the 6 to 12 months after the filing.…”
Section: Discussionmentioning
confidence: 99%
“…One set relies on emergency room (ER) discharge data (Berger et al 2011; Huang et al 2011; Wood et al 2012, 2015); the other set has relied on data on investigations and substantiations from Child Protective Services (CPS) agencies (Steinberg, Catalano, and Dooley 1981; Seiglie 2004; Ben-Arieh 2010; Millett, Lanier, and Drake 2011; Lindo, Schaller, and Hansen 2013; Nguyen 2013; Frioux et al 2014). The distinction is important as ER data are likely to capture more severe instances of child maltreatment, specifically injuries associated with physical abuse, whereas CPS data measure all types of child maltreatment, regardless of severity (we return to this point below; Widom 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies using CPS data find that economic downturns are associated with higher rates of child maltreatment investigations and substantiations (Seiglie 2004; Ben-Arieh 2010; Lindo et al 2013; Frioux et al 2014; Berger et al 2015). Others report that the relationship between child maltreatment rates and the unemployment rate varied across states or counties within a state (Steinberg et al 1981; Millett et al 2011; Nguyen 2013), and one study finds no significant relationship (Bitler and Zavodny 2004).…”
Section: Introductionmentioning
confidence: 99%